2016
DOI: 10.1111/cup.12721
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative lesion of anogenital mammary‐like glands in the setting of Cowden syndrome: case report and review of the literature

Abstract: Mammary-like glands are normal appendages of anogenital skin and can give rise to epithelial and stromal tumors that closely resemble breast tumors. Cowden syndrome is an autosomal-dominant cancer-predisposition syndrome that is associated with increased risk of various benign and malignant tumors including breast cancers. Here, we report the first case of a proliferative lesion of mammary-like glands in the setting of Cowden syndrome. A 27-year-old female with Cowden syndrome (R130Q-PTEN mutation) presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…He described cutaneous glands in the anogenital region (predominantly the anus, labia and vulva), accounting for fibroadenomatous changes found beyond the extent of the milk line. While fibroadenomas are very common in the breast, there are only about 40 cases described in the anogenital region (3) and only six of which were perianal rather than vulvar (1,(4)(5)(6)(7)(8). In most instances, the anogenital lesion was a well circumscribed, solitary mass that varied in size from 0.8 to 6 cm.…”
Section: Discussionmentioning
confidence: 99%
“…He described cutaneous glands in the anogenital region (predominantly the anus, labia and vulva), accounting for fibroadenomatous changes found beyond the extent of the milk line. While fibroadenomas are very common in the breast, there are only about 40 cases described in the anogenital region (3) and only six of which were perianal rather than vulvar (1,(4)(5)(6)(7)(8). In most instances, the anogenital lesion was a well circumscribed, solitary mass that varied in size from 0.8 to 6 cm.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Hedayat et al reported a case of a 27-year-old woman with Cowden syndrome with a perianal lesion demonstrating proliferative changes strikingly similar to those commonly seen in breast tissue (19).…”
Section: Introductionmentioning
confidence: 99%
“…5 Certain genodermatoses (ie, Cowden syndrome) also may predispose patients to benign or malignant pathology in ABT. 6 We present a rare case of accessory breast cancer in the inframammary region masquerading as a cyst. These findings were further supported by ultrasonography and mammography.…”
mentioning
confidence: 99%